The Effect of Commercially Available Sugar Alternatives on Bacillus Probiotic Viability During Baking - Jessie Payne; Brooke Holt; Danielle Bellmer; Destiny Wahweah (International Journal of Food Science)
Growing health concerns regarding sucrose consumption have led to an increased use of alternative sugars, including sugar alcohols, artificial sweeteners, and natural sweeteners. This study investigated the impact of commercially available sugar substitutes on the viability of Bacillus probiotics and Lactobacillus strains during baking. Our findings revealed that Bacillus subtilis strains exhibited the highest log reduction with sucralose (average 0.99 log CFU/g) and the lowest with monk fruit (average 0.60 log CFU/g). In contrast, Lactobacillus acidophilus demonstrated a higher log reduction, with the highest reduction observed with monk fruit (4.18 log CFU/g) and the lowest with sucralose (3.47 log CFU/g). Notably, B. subtilis strains exhibited significantly greater viability during baking compared to L. acidophilus (p<0.05). Furthermore, Bacillus probiotics maintained their viability even under high-temperature baking conditions, suggesting their potential for use in baked goods as a viable probiotic ingredient. Additionally, the use of sugar alternatives, such as monk fruit, sucralose, and stevia, was found to significantly increase the water activity in baked cookies, which may contribute to decreased stability and preservation of probiotic efficacy. This study underscores the superior stability of Bacillus probiotics in baked products and highlights the potential benefits of using sugar substitutes to enhance both product shelf life and health benefits.